Numerical Study on the Thermal Insulation of Smart Windows Embedded with Low Thermal Conductivity Materials to Improve the Energy Efficiency of Buildings - Zakaria N.M.; Omar M.A.; Mukhtar A. (Penerbit Akademia Baru, 2024)
The building industry accounts for almost 40% of the world's energy consumption. To reduce the global heat transfer coefficient, sustainable buildings should use highly insulated enclosures. As the building envelope serves as a barrier between the exterior and interior of the building, integration of passive solar design principles in its construction, such as smart windows with low thermal conductivity materials are essential. Smart windows may assist to reduce energy consumption by minimizing heat gain by the building, which able reduce the cooling loads while maintaining the thermal comfort for the building users. This study features smart double-glazed windows filled with low thermal conductive materials which are argon and aerogel to improve window insulation in pursuit of energy efficiency improvement. A numerical model is developed in ANSYS Workbench to evaluate thermal insulation performance of argonfilled and aerogel-filled windows by measuring the indoor surface temperature of the building at three critical times of the day. Newton's Law of Cooling is used to compute the empirical value of the heat transfer across the window to compare and validate the numerical data. This study shows that argon-filled and aerogel-filled window able to reduce the heat transfer across the building up 21% and 59% respectively. Aerogel is proven to resist more heat transfer as compared to argon. 2023, Penerbit Akademia Baru. All rights reserved.